2017
DOI: 10.1017/ice.2017.162
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Disinfectants Against Candida auris and Other Candida Species

Abstract: Contaminated surfaces are a suspected source for dissemination of the globally emerging pathogen Candida auris. In laboratory testing, sporicidal and improved hydrogen peroxide disinfectants were highly effective against C. auris, C. glabrata, and C. albicans. The widely used quaternary ammonium disinfectants exhibited relatively poor activity against all of the Candida species. Infect Control Hosp Epidemiol 2017;38:1240-1243.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
152
1
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 163 publications
(165 citation statements)
references
References 5 publications
3
152
1
3
Order By: Relevance
“…The explanation for this was most likely the use of surface cationic‐active products, as it was not known until very recently that these products, as well as quaternary ammonium disinfectants, cannot effectively remove C. auris from surfaces. At present, it has been recommended to use disinfectants with sporicidal activity or hydrogen peroxide‐based products to clean surfaces in rooms of patients infected or colonised with C. auris due to its high efficiency in removing this species from inert surfaces . Furthermore, the capacity of C. auris to survive and persist for several days in clinical environments is well known and facilitates a potential route for dissemination of this emerging and multidrug‐resistant pathogen…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The explanation for this was most likely the use of surface cationic‐active products, as it was not known until very recently that these products, as well as quaternary ammonium disinfectants, cannot effectively remove C. auris from surfaces. At present, it has been recommended to use disinfectants with sporicidal activity or hydrogen peroxide‐based products to clean surfaces in rooms of patients infected or colonised with C. auris due to its high efficiency in removing this species from inert surfaces . Furthermore, the capacity of C. auris to survive and persist for several days in clinical environments is well known and facilitates a potential route for dissemination of this emerging and multidrug‐resistant pathogen…”
Section: Resultsmentioning
confidence: 99%
“…This feature could be due to the use of cationic surface‐active products like quaternary ammonium, disinfectants that until very recently its efficacy against this species was unknown. Currently, the activity of sporicidal disinfectants and hydrogen peroxide‐based disinfectants against C. auris has been demonstrated . Likewise, many colonised biomedical devices could be also implicated in cross‐infection, maintenance of reservoirs and therefore persistence of an outbreak …”
Section: Introductionmentioning
confidence: 99%
“…149 The susceptibility of C auris to germicides (ie, antiseptics and disinfectants) has been studied by several investigators. 139,144,[150][151][152][153] Rutala et al 153 assessed the germicidal activity of high-level disinfectants and/or chemical sterilants and reported that all agents (ie, 0.20% peracetic acid, 2.4% glutaraldehyde, 0.65% hydrogen peroxide plus 0.14% peroxyacetic acid, 2% accelerated hydrogen peroxide) achieved a ≥4.1-log 10 reduction of C auris with the exception of 0.55% ortho-phthalaldehyde that achieved only a 2.3-log 10 inactivation for E coli. Importantly, these in vitro experiments were done under challenging conditions (ie, 5% fetal calf serum and 1-minute exposure time).…”
Section: Susceptibility To Germicidesmentioning
confidence: 99%
“…auris . Other products resulting in ≥5 log 10 CFU reduction include hydrogen peroxide (1.4%), peracetic acid (1200 ppm) with hydrogen peroxide (<1%) and acetic acid, and improved hydrogen peroxide (0.5%) . Ethyl‐alcohol (29.4%) produced a <3 log 10 CFU reduction …”
Section: Infection Prevention and Control Measuresmentioning
confidence: 99%